Drivers of temporal changes in temperate forest plant diversity vary across spatial scales. (27th July 2015) - Bernhardt‐Römermann, Markus; Baeten, Lander; Craven, Dylan; De Frenne, Pieter; Hédl, Radim; Lenoir, Jonathan; Bert, Didier; Brunet, Jörg; Chudomelová, Markéta; Decocq, Guillaume; Dierschke, Hartmut; Dirnböck, Thomas; et al.
Abstract Global biodiversity is affected by numerous environmental drivers. Yet, the extent to which global environmental changes contribute to changes in local diversity is poorly understood. We investigated biodiversity changes in a meta‐analysis of 39 resurvey studies in European temperate forests (3988 vegetation records in total, 17–75 years between the two surveys) by assessing the importance of (i) coarse‐resolution (i.e., among sites) vs. fine‐resolution (i.e., within sites) environmental differences and (ii) changing environmental conditions between surveys. Our results clarify the mechanisms underlying the direction and magnitude of local‐scale biodiversity changes. While not detecting any net local diversity loss, we observed considerable among‐site variation, partly explained by temporal changes in light availability (a local driver) and density of large herbivores (a regional driver). Furthermore, strong evidence was found that presurvey levels of nitrogen deposition determined subsequent diversity changes. We conclude that models forecasting future biodiversity changes should consider coarse‐resolution environmental changes, account for differences in baseline environmental conditions and for local changes in fine‐resolution environmental conditions.